A case of Bochdalek hernia with anomalous hepatic lobe heterotopia-case report - Wajiha Khan; Adnan Safi; Asrar Ahmad; Mehwish Mooghal (SpringerOpen, 2021)
Abstract Background Bochdalek hernia is the most common type of congenital diaphragmatic hernia (CDH) resulting from postero-lateral diaphragmatic defect. Hepatic heterotopia is very rarely associated with CDH, and hepatic herniation favors the worst prognosis. Case presentation We present a case of a neonate diagnosed with right Bochdalek hernia (BH) with anomalous hepatic lobe heterotopia. Intra operatively, mal-rotated loops were also found to be herniating in the right hemithorax. The mal-rotated loops were reduced back into abdomen after performing Ladd's procedure and diaphragmatic defect was repaired over the anomalous liver lobe. Baby was discharged on 7th postoperative day and follow-ups showed good recovery. Conclusion This case report discusses the presentation, classification, and significance of this association. Our case report is noteworthy as Bochdalek hernia is very rarely associated with anomalous hepatic lobe.